PENGARUH REWARD DAN PUNISHMENT TERHADAP KINERJA KARYAWAN PT. BANK MANDIRI, TBK - Puji Priyadi; Siwi Nur Indriyani (Jurnal Ekonomi dan Industri, 2020)
To determine the effect of reward and punishment on the performance of the employees PT. Bank Mandiri (Persero), Tbk Jakarta. The research method uses qualitative and quantitative descriptive analysis, the analysis model used is linear regression both simply and multiple. The study population of all employees of PT. Bank Mandiri (Persero), Tbk Jakarta marketing department which numbered 175 employees. The sampling technique of this study used simple random sampling. This study uses a sample size with the Slovin formula and obtained as many as 64 respondents. Result reward and punishment have positive and significant effect on the performance of the employees of PT. Bank Mandiri (Persero), Tbk Jakarta both partially and simultaneous.